Modern Dreams : The Rise and Fall and Rise of Pop. - The Institute for Contemporary Art, New York (Cambridge : the MIT press, 1988)
Alloway, Lawrence ; Banham, Reyner ; Barry, Judith ; Castelli, Leo ; Coplans, John ; Finkelpearl, Tom ; Frampton, Kenneth ; Halle, Howard ; Hamilton, Richard ; Hebdige, Dick ; Heiss, Alanna ; Johnson, Betsey ; Lawson, Thomas ; Leffingwell, Edward ; Lichtenstein, Roy ; Oldenburg, Claes ; Phillips, Patricia ; Smithson, Alison and Peter ; Tsai, Eugenie ; Wallis, Brian ; Wess, Glenn ; Whitham, Graham
Modern Dreams : The Rise and Fall and Rise of Pop, accompanies the "The Pop Project", a series of exhibitions presented by The Institute for Contemporary Art developed for The Clocktower Gallery, New York, from October 22, 1987, through June 12, 1988.
boek